2011
DOI: 10.1002/pmic.201100077
|View full text |Cite
|
Sign up to set email alerts
|

Novel serum protein biomarkers indicative of growth hormone doping in healthy human subjects

Abstract: The detection of recombinant human growth hormone (rhGH) is difficult due to its short half-life; therefore, novel and robust biomarkers of rhGH abuse are needed. In this study, serum samples derived from subjects treated with rhGH in a randomized, double blind, placebo-controlled crossover study were analyzed by 2-DE coupled with MS. Eight healthy male subjects aged 23.2 ± 0.6 yr were injected with rhGH (2 mg/day) or saline for 7 days with serum samples drawn at days 0, 3, and 8. Protein intensities were quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“…The other proteins investigated, VDBP and decorin, did not change in their respective levels during or after the recGH administration, indicating that these proteins are not likely to be informative biomarkers of GH administration in athletes. It needs to be emphasized that in addition to the proteins studied here, some other putative GH biomarkers from omics studies warrant confirmation such as apolipoprotein L1, alpha‐HS‐glycoprotein, lumican, alpha‐1 antitrypsin, total plasma transthyretin, and hemoglobin β subunit 16,26 …”
Section: Discussionsupporting
confidence: 88%
“…The other proteins investigated, VDBP and decorin, did not change in their respective levels during or after the recGH administration, indicating that these proteins are not likely to be informative biomarkers of GH administration in athletes. It needs to be emphasized that in addition to the proteins studied here, some other putative GH biomarkers from omics studies warrant confirmation such as apolipoprotein L1, alpha‐HS‐glycoprotein, lumican, alpha‐1 antitrypsin, total plasma transthyretin, and hemoglobin β subunit 16,26 …”
Section: Discussionsupporting
confidence: 88%
“…We also identified apolipoprotein A-1, alpha-1 antitrypsin, and inter-alpha trypsin inhibitor heavy chain H4 proteins as differentially expressed in one of the analysis Phases only, so, were not evaluated further. Interestingly, previous studies have reported these three proteins to be differentially expressed in rGH or CJC-1295 (an analogue of growth hormone releasing hormone), administered subjects, so while they were not followed further by us, some concordance was observed 21 , 22 .…”
Section: Resultsmentioning
confidence: 80%
“…2D Western blotting was used to validate the three isoforms, because a normal WB would not have allowed distinguishing between the different isoforms (all with very similar molecular weight), since the antibodies were not raised against one of the specific isoforms of the proteins. Therefore, the only way to distinguish between them was to separate the different isoforms by 2-DE prior to the immunochemical reaction [ 15 ]. Western blotting and 2D Western blotting protein expressions were significantly higher in the leiomyoma compared to the myometrium, confirming the results obtained from the 2-DE analysis ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%